Front Cover: Upregulation of the Glutaminase II Pathway Contributes to Glutamate Production upon Glutaminase 1 Inhibition in Pancreatic Cancer. Issue 21 (12th November 2019) - Udupa, Sunag; Nguyen, Stephanie; Hoang, Giang; Nguyen, Tu; Quinones, Addison; Pham, Khoa; Asaka, Ryoichi; Nguyen, Kiet; Zhang, Cissy; Elgogary, Amira; Jung, Jin G.; Xu, Qingguo; et al.
Abstract : DOI: 10.1002/pmic.201800451 Much like the classic arcade game "Whack‐a‐Mole", cancer cells are able to upregulate a different metabolic pathway when one pathway is inhibited. Specifically, using metabolomics technologies with isotopic labelling, Sunag Udupa et al. demonstrate in article number 1800451 the production of glutamate from glutamine via the glutaminase II pathway when the glutaminase 1 pathway is inhibited. This metabolic adaptability of tumors justifies the need for targeting multiple metabolic pathways, aiming at both main and adaptive metabolic networks.